Apotransferrin-induced recovery after hypoxic/ischaemic injury on myelination - Guardia Clausi, Mariano (2010)
We have previously demonstrated that aTf (apotransferrin) accelerates maturation of OLs (oligodendrocytes) in vitro as well as in vivo. The purpose of this study is to determine whether aTf plays a functional role in a model of H/I (hypoxia/ischaemia) in the neonatal brain. Twenty-four hours after H/I insult, neonatal rats were intracranially injected with aTf and the effects of this treatment were evaluated in the CC (corpus callosum) as well as the SVZ (subventricular zone) at different time points. Similar to previous studies, the H/I event produced severe demyelination in the CC. Demyelination was accompanied by microglial activation, astrogliosis and iron deposition. Ferritin levels increased together with lipid peroxidation and apoptotic cell death. Histological examination after the H/I event in brain tissue of aTf-treated animals (H/I aTF) revealed a great number of mature OLs repopulating the CC compared with saline-treated animals (H/I S). ApoTf treatment induced a gradual increase in MBP (myelin basic protein) and myelin lipid staining in the CC reaching normal levels after 15 days. Furthermore, significant increase in the number of OPCs (oligodendroglial progenitor cells) was found in the SVZ of aTf-treated brains compared with H/I S. Specifically, there was a rise in cells positive for OPC markers, i.e. PDGFRα and SHH+ cells, with a decrease in cleaved-caspase-3+ cells compared with H/I S. Additionally, neurospheres from aTf-treated rats were bigger in size and produced more O4/MBP+ cells. Our findings indicate a role for aTf as a potential inducer of OLs in neonatal rat brain in acute demyelination caused by H/I and a contribution to the differentiation/maturation of OLs and survival/migration of SVZ progenitors after demyelination in vivo.